Высокочувствительный СВЧ измеритель влагосодержания в неполярных диэлектрических жидкостях на основе ступенчатого неоднородного коаксиального резонатора - Рудаков, В.В.; Коробко, А.А. (Електротехніка і електромеханіка, 2016)
Рассматривается высокочувствительный измеритель влагосодержания в неполярных жидких диэлектриках.
Аргументированы пути повышения чувствительности классического диэлькометрического метода. Приводиться
описание разработанной конструкции измерителя влажности на основе ступенчатого неоднородного коаксиального
резонатора. Рассмотрены результаты анализа резонансных характеристик измерительного преобразователя, а
также определены величины объемного влагосодержания смесей трансформаторное масло – вода в диапазоне
влагосодержания (10 – 10⁴) cм³/м³ Розглядається високочутливий вимірювач вмісту вологи в неполярних рідких діелектриках. Аргументовано шляхи
підвищення чутливості класичного діелькометричного методу. Приводиться опис розробленої конструкції
вимірювача вологості на основі ступеневого неоднорідного коаксіального резонатора. Розглянуто результати аналізу
резонансних характеристик вимірювального перетворювача, а також визнченi величини об'ємного вмісту вологи
сумішей трансформаторне масло – вода в діапазоні вмісту вологи (10 – 10⁴) cм³/м³ Purpose. Objective is to create a moisture meter for non-polar
liquid dielectrics with low volumetric moisture content of more
than 10⁻³ %. Methodology. Moisture measuring is based on dielcometric method. It is implemented as a resonant method of determining a capacitance measuring transducer. Measuring transducer capacitive type has a working and parasitic capacitance. It
was suggested the definition of moisture on four of resonance
frequencies: when the measuring transducer is turned off, one by
one filled with air, «dry» and investigated liquid, to determine the
parasitic capacitance of the measuring generator, and the parasitic capacitance of the measuring transducer and humidity.
Measurement frequency was increased up to microwave range to
increase the sensitivity. Measuring transducer with distributed
parameters representing a step heterogeneous coaxial resonator
is used by. This measuring transducer has a zero stray capacitance, because the potential electrode has a galvanic connection
with an external coaxial electrode. Inductive ties loop is used to
neglect parasitic capacitance of the measuring generator, and to
increase the quality factor of the system. Measuring moisture is
reduced to measuring the two frequencies of resonance frequency
and «dry» and investigated liquid. Resonant characteristics
transducer in a step inhomogeneous coaxial resonator have been
investigated to determine the quality factor of filled with air and
transformer oil, and experiments to measure the moisture content
in transformer oil have been conducted. Results. Measuring
transducer of distributed type is developed and researched – it is
step inhomogeneous coaxial resonator. It has a smaller geometric
length and larger scatter of the first and second resonant frequencies. Expression is obtained for determination of moisture on the
basis of two resonant frequencies. The formula of the two frequencies to determine the moisture is correct. Resonant characteristics are obtained for measuring transducer. Its quality factor
has been determined – it does not depend on what it is filled with
air or oil. The moisture content in transformer oil for the amount
of water to 10-3 % with an error of no more than 6.7 % has been
determined. Originality. It has been proposed to use of an inhomogeneous step coaxial resonator as a measuring transducer.
Original high sensitive moisture meter for the fluid at rest and
flowing fluid with low values of parasitic capacitances has been
developed and researched. An original method of determining the
moisture by measuring the two frequencies of resonance has been
proposed and implemented. Practical value. This meter may be
used to determine moisture in any of the non-polar liquid with
high speed and accuracy. Moisture meter can be used in electrical
engineering, aeronautical engineering, in the chemical and food
industries